2023
DOI: 10.32604/iasc.2023.030142
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Vehicle Assisted Forest Fire Detection Using Deep Convolutional Neural Network

Abstract: Disasters may occur at any time and place without little to no presage in advance. With the development of surveillance and forecasting systems, it is now possible to forebode the most life-threatening and formidable disasters. However, forest fires are among the ones that are still hard to anticipate beforehand, and the technologies to detect and plot their possible courses are still in development. Unmanned Aerial Vehicle (UAV) image-based fire detection systems can be a viable solution to this problem. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…A technique for recognising forest fires was proposed by Rahman et al [18] using a Convolutional Neural Network (CNN) architecture and freshly created fire detection dataset from another study. Their approach utilised separable convolution layers for rapid fire detection, making it suitable for real-time applications.…”
Section: Related Workmentioning
confidence: 99%
“…A technique for recognising forest fires was proposed by Rahman et al [18] using a Convolutional Neural Network (CNN) architecture and freshly created fire detection dataset from another study. Their approach utilised separable convolution layers for rapid fire detection, making it suitable for real-time applications.…”
Section: Related Workmentioning
confidence: 99%
“…Strengthening FMU capacity will significantly improve forest fire control performance. In a recent study [44], Rahman et al proposed a method for detecting forest fires using a deep convolutional neural network based on the dataset for Forest Fire Detection from Mendeley Data. Experimental results of this research showed that the method could identify forest fires within images with an accuracy of 97.63% and a F1 score of 98%.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Unlike machine learning algorithms, deep learning automatically extorts and familiarizes complex feature representations [47]. "CNN-based models utilize frames from surveillance systems as input, and the predicted result is sent to an alert system [44].…”
Section: Introductionmentioning
confidence: 99%